Clinico-Therapeutic Studies On Mycotic Dermatitis Of Dogs - Vinu David P (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 1998)
Incidence of mycotic dermatitis among the total canine cases presented at the University Veterinary ,Hospitals, Kokkalai and Mannuthy for a period from September 1996 to August 1998 was found to be 5.13 per cent. Among the total